The role of emotional contagion dimensions on depression, anxiety and post-traumatic stress disorder of hospital staff during Covid-19 epidemic - Khesali, Maryam; akibakhshMohammadi, Nasim; Bahadoriyan Lotfabadi, Nahid; Bakhtiari, Maryam; Kianimoghadam, Amir Sam (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: Various studies have investigated the role of emotional contagion in various emotional disorders, but the role of emotional contagion dimensions in the psychological symptoms during the Covid-19 epidemic has not been investigated. Therefore, the aim of this study was to investigate the dimensions of emotional contagion on depression, anxiety and post-traumatic stress disorder of hospital staff during the Covid-19 epidemic. Materials and Methods: This was cross-sectional descriptive correlational study. The present study population consisted of hospital staff of Shahid Beheshti University of Medical Sciences who were selected by convenience and with the help of inclusion criteria in the winter of 1399 that 200 people were selected by Convenience Sampling and measured by Depression Anxiety Scale (DASS)(PTSD check list for DSM5 (PCL-5) and the Emotional contagion Scale. Results: The dimensions of emotional contagion can explain 18% of the variable changes in the criterion of depression. The dimensions of emotional contagion can explain 28% of the variable changes in the anxiety criterion. The dimensions of emotional contagion can explain 43% of the variable changes in the post-traumatic stress disorder criterion. Conclusions: According to the findings of the present study, it can be concluded that education about emotional contagion and awareness of its effect on psychological problems play an important role in improving the psychological condition of hospital staff in pandemic conditions.